SYSTEMATIC LITERATURE REVIEW: DISASTER RESILIENCE EDUCATION IN THE SCHOOL CURRICULUM IN INDONESIA - Hardiant Terrent Zetta Mahendra; Aji Prasetyo (Universitas Labuhanbatu, 2026)
Purpose – The purpose of this literature review is to review, evaluate, and synthesize existing research findings and ideas to form a new, more comprehensive picture of the application of disaster resilience education in school curricula in Indonesia.Methodology – This study uses the Systematic Literature Review (SLR) methodology, a scientific investigation that examines the integration of disaster resilience education into the Indonesian school curriculum. This article examined 55 scientific works published from 2015 to 2025 (the last 10 years) related to disasters, curriculum, and mitigation. The approaches used include curriculum integration through the Disaster-Safe Education Unit (SPAB) program, strengthening values of local wisdom, and disaster risk reduction (DRR) grounded in environmental education.Findings – Research shows that implementing disaster education in educational units can increase students' awareness, skills, and responsiveness to threats before and after a disaster. However, there are obstacles such as budget constraints, lack of ongoing training, and minimal supporting facilities.Contribution – This article provides strategic recommendations to strengthen the interconnectedness among the government, schools, and communities to support an adaptive, sustainable disaster curriculum. Thus, adequate and structured disaster education is expected to create a resilient generation prepared to face disaster risks from an early age.